2011
DOI: 10.1103/physreva.84.013606
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of spin coherence in a spin-1 Bose-Einstein condensate by dynamical decoupling approaches

Abstract: We study the enhancement of spin coherence with periodic, concatenated, or Uhrig dynamical decoupling N -pulse sequences in a spin-1 Bose condensate, where the intrinsic dynamical instability in such a ferromagnetically interacting condensate causes spin decoherence and eventually leads to a multiple spatial-domain structure or a spin texture. Our results show that all the three sequences successfully enhance the spin coherence by pushing the wave vector of the most unstable mode in the condensate to a larger … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Dynamical decoupling techniques such as quantum bang-bang control [7], in which undesired environmental interactions are averaged out by repeated application of suitable pulses, provides one powerful solution for this purpose. By application of dynamical decoupling, it has been theoretically shown that spin coherence can be prolonged in a spin-1 Bose gas [8]. Furthermore, the effects of weak magnetic dipole-dipole interactions (MDDIs) have been revealed [9] and controlled using dynamical decoupling techniques [10].…”
Section: Introductionmentioning
confidence: 98%
“…Dynamical decoupling techniques such as quantum bang-bang control [7], in which undesired environmental interactions are averaged out by repeated application of suitable pulses, provides one powerful solution for this purpose. By application of dynamical decoupling, it has been theoretically shown that spin coherence can be prolonged in a spin-1 Bose gas [8]. Furthermore, the effects of weak magnetic dipole-dipole interactions (MDDIs) have been revealed [9] and controlled using dynamical decoupling techniques [10].…”
Section: Introductionmentioning
confidence: 98%
“…However, the resonant dipolar magnetization dynamics can be revealed under current experimental conditions if we employ dynamical decoupling techniques to cancel the Zeeman effect [1,28,32]. In particular, by applying frequent π x pulse, which rotates the condensate spin 180 o along x-axis, the Zeeman effect is eliminated while leaving the dipolar interaction intact to the leading order.…”
Section: Suppressing the Zeeman Effect Of An External Strong Magnmentioning
confidence: 99%
“…Recently, with the precision measurement of an ultraweak or zero magnetic field, the investigation of the nonsecular dipolar interaction effects becomes revived in the areas of zero-field nuclear magnetic resonance and dipolar spinor Bose-Einstein condensates [7][8][9][10][11]. Particularly, the achievements in spinor Bose-Einstein condensates (BECs) provide a highly tunable and controllable system where the spin interactions, including the magnetic dipolar interaction, can be accurately engineered [3,[12][13][14][15][16][17][18][19]. Such dipolar spinor condensates make them an ideal testbed to extensively explore the full magnetic dipolar interaction effect, including not only the secular part but also the nonsecular one which breaks the rotational symmetry and definitely brings new physics.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it is highly desired to suppress one spin interaction and make the other dominant. Although efforts have been made to prohibit either the dipolar interaction [21] or the spin exchange interaction [23,24], it is yet difficult to clearly separate the individual effects.…”
mentioning
confidence: 99%
“…In this paper, we propose to independently suppress the dipolar and the spin-exchange interaction by a sequence of rf pulses ( Fig. 1) and optical Feshbach periodic dynamical decoupling (PDD) sequences [24], respectively. This scheme was verified by the analytic derivations, demonstrating that the manipulations of the relative strength between the two spin interactions enable experimentalists to unambiguously distinguish the specific role of the dipolar and the spin-exchange interactions.…”
mentioning
confidence: 99%